PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 20 PADANG - Asnita, Asnita; Gani, Erizal (Universitas Negeri Padang, 2020)
ABSTRACTThe purpose of this research was to describe things as follows. First, describes the skill level of writing the text explanatory grade VIII SMPN 20 Padang before using the the Discovery Learning model. Second, decsribes the skill level of writing the text explanatory grade VIII SMPN 20 Padang after using the Discovery Learning model. Third, analyzing the influence of use Discovery Learning model ti the skill level of the writing text explanatory grade VIII SMPN 20 Padang. This research used quantitative research which experimental method. This research draft is One Group Pretest and Posttest Design. Based on the reslt of the study, the following three things concluded. First, the explanatory text writing skills before using the Discovery Learning model of grade VIII SMPN 20 Padang are in qualification more than enough (LdC) with an average of 68,55. Second, the explanatory text writing skills after using the Discovery Learning model of eighth grade students of SMPN 20 Padang are in good qualifications (B) with an average of 79,00. Third, besed on t-test, the alternative hypothesis (H1) is aceepted at the 95% significant level and the degree of freedom (dk)= (n1+n2)-2 because tcount>ttable, which is 4,13>1,70. Kata Kunci: Pengaruh, Model Discovery Learning, Keterampilan Menulis, Teks Eksplanasi